Penerapan Teknik Terapi Hipnosis Lima Jari Terhadap Kecemasan Pasen Lansia Dengan Hipertensi Melalui Aplikasi Teori Hildegard E Peplau Di Puskesmas Sawah Lebar Bengkulu Tahun 2025 - Novelia, Novelia; Hidayat, Yance (Utami Publisher, 2025)
Hypertension is one of the chronic cardiovascular diseases that is a major cause of morbidity and mortality worldwide. Anxiety is a psychological factor that can influence hypertension. If this condition persists without proper management, it may affect the quality of life of the elderly (Hasniati et al., 2022). Five-finger hypnosis therapy is a relaxation technique in which individuals create pleasant imagery, concentrate on it, and gradually release their attention from anxiety.